Black Spider-Man – masks, power and identity in a 21st century superhero world - Smurthwaite, James Edward (My University, 2017)
In November 2011 Marvel Comics introduced the re-imagined incarnation of one of their top tier superhero characters, Spider-Man. Marvel proposed the new identity of the hero as Miles Morales, a 13-year-old boy of African American descent. It represents the first significant alteration to the character in almost half a century. Further, Marvel suggested that Miles is evidence of both their commitment to diversity, transformation and the representation of a multicultural society that includes different identity propositions. This study explores the enunciation on of Miles’ identity counterpoised with that of the normative discursive enunciation of heroism in comics within the context of intersectional politics. A central focus is the manner in which Miles’ rendering can be interpreted as discursively disruptive and transformative, especially in the depiction of race and class. The study views Marvel’s representation of Miles as not only a proposition of black postcolonial heroism but also that of the scaffolding of power and knowledge. It is the contention of this study that UCSM exhibits the markings of colonial and imperial discourse pertaining to identity politics, manifesting in the discursive strategy of mimicry and the mimetics of popular culture, that reveal firmly entrenched power relations limiting Miles’ autonomy. The analysis delves into the articulation of race in the circumscription and demarcation of identity, when read comparatively with classical heroism, supporting characters and the subjectivity of Miles’ white counterparts, notably his predecessor as Spider-Man, Peter Parker. Miles is imprinted with the pattern of disenfranchisement and labours under the weight of racialised identity politics that invoke the spectre of colonialism. Through the use of critical discourse analysis, postcolonial and critical theory the study brings to light the maintenance and structure of inequality, tacit discrimination and stereotypical identity that surfaces in a 21st century popular cultural text.
A dissertation submitted to the Faculty of Humanities, in fulfilment of the requirements for the degree of Doctor of Philosophy at the University of the Witwatersrand, Johannesburg, 2017
Keywords: Comic books, strips, etc.--History|y21st century; Superheroes--Comic books, strips, etc.--21st century